Cheluridae - Coleman, Charles Oliver; Renz, Adina (Zootaxa, 2009)
Tropichelura insulae (Calman, 1910), a species living in excavations in wooden logs together with limnoriid Isopoda, is redescribed from Lizard Island, Great Barrier Reef Australia. This species has enlarged first gnathopods, three teeth on the posterior margin of pleonite 3 and the peculiar uropods and telson that are characteristic for the family Cheluridae.